(untitled) (International Journal of Engineering and Computer Science, 2016)
Internet provides various resources for Remote health services. Web based communication models are adapted to manage the interaction between the remote people with medical experts. Remote health services are provided in two ways. They are reputable portals and community based health services. Reputable portal provides information related to the health care domains. Community based health services are built to support in a particular way based on health care solutions for the patients.